A saúde sexual e reprodutiva dos estudantes universitários: a percepção dos profissionais da saúde de uma universidade pública - Schuster, Fabianne Banderó (2024)
Addressing the sexual and reproductive health of university students is crucial, given the vulnerability of this population to risky behaviors. The unhealthy behaviors prevalent in this group increase their exposure to these risks, highlighting the need for reflections and interventions tailored to the specific demands of university students. This project investigates the perceptions and experiences of health professionals at a public institution in Rio Grande do Sul, with the aim of understanding how they manage the care of students' sexual and reproductive health. The theoretical framework is based on concepts of sexual and reproductive health, as well as on health promotion and education as tools to improve the quality of life of university students. The study employs a qualitative method, characterized as a case study with an exploratory approach, using semi-structured interviews with the institution's health professionals. The main findings emphasize the need to improve the training of professionals and the provision of sexual health services on campus, in addition to the importance of integrating health education with care practices to promote more effective interventions. However, the research faces limitations, such as the reliance on the subjective perceptions of the interviewees and the restriction of the study to a single institution, which may limit the generalization of the results. These findings reinforce the urgency of developing educational and health promotion strategies that are better adapted to the needs of the university population.